Two new species of Dyssochroma (Solandreae, Solanaceae) and an updated identification key to the genus - Silva, Gabriel Barros Da; Jesus, Rodrigo José Araújo De; Giacomin, Leandro Lacerda; Stehmann, João Renato; Cardoso, Pedro Henrique; Silva, Tânia Regina Dos Santos (Phytotaxa, 2025)
Dyssochroma is a small genus of Solanaceae endemic to Brazil, previously known to include three species occurring in the Atlantic Forest domain. Here, we describe two new species of the genus: D. caatingae, from the Caatinga domain in Pernambuco state, and D. jardimii, from the Atlantic Forest domain of Bahia state. The two new species are characterized by a pubescent indumentum in the young branches, calyces, and corollas, with multicellular non-glandular trichomes, whereas their congeners are glabrous or glabrescent, with sparse, unicellular, non-glandular trichomes. Dyssochroma caatingae has a variety of non-glandular trichomes, including simple and branched, ovate leaf blades, and ovary 5–6 × 6 mm. Diagnostic traits of D. jardimii include leaves with revolute margins and trichomes concentrated along the midvein, and green corollas with purplish to brownish stripes. We provide detailed descriptions, illustrations, field photographs, a distribution map, and taxonomic notes for both new species. This study increases the number of recognized species in Dyssochroma from three to five. Additionally, we present an identification key to distinguish them.